Effect of the execution order from concurrent exercise session on blood pressure responses in hypertensive older men - Denise Rodrigues Fernandes; Tássia Magnabosco Sisconeto; Sara Silva Freitas; Tállita Cristina Ferreira Souza; Rodrigo Sudatti Delevatti; Rodrigo Ferrari; Guilherme Morais Puga; Ana Carolina Kanitz (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To compare blood pressure (BP) responses among the different orders of execution of concurrent exercise (CE) sessions in controlled hypertensive older men. Methods: Fifteen older men (64 ± 5 years) participated in three randomized crossover sessions: control session (C), CE in aerobic-resistance order (AR), and resistance-aerobic order (RA). The CE was performed for 1 h, in which 30 min were for the resistance exercise with 5 exercises at 70% of 1RM and 30 min for the aerobic exercise on a treadmill with intensity corresponding to the first ventilatory threshold. Clinical systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean blood pressure (MBP) were measured at rest and over 2 h and 24 h after the session. For analysis, the Generalized Estimating Equations (GEE) test was used with Bonferroni's complimentary test (α = 0.05). Results: The SBP decreased by 30 min after AR, while after RA we obtained reductions during 1 h after a session concerning rest. Between sessions, we found lower values in both CE compared to the C at 30 min, 45 min, and 90 min. In the RA there was a lower pressure in relation to the C at minute 60. The DBP reduced 30 min after the AR regarding the pre-session, however with no difference between sessions. The MBP was lower in relation to 30 min rest after AR. Among sessions, a pressure drop was observed in the AR compared to the C at 30 min and 45 min. Conclusion: We can conclude that the CE was effective in generating post-exercise hypotension regardless of the order in controlled hypertensive older men.